2016
DOI: 10.4103/0974-7753.179384
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with premature hair graying in a young Indian population

Abstract: Context:Although the primary cause of premature hair graying (PHG) is considered to be genetic, certain environmental factors also play a role. Trace element deficiencies such as Vitamin B12, Vitamin D3, and calcium may also be associated with PHG. However, India-specific data are relatively sparse.Aims:The present study aimed at identifying factors associated with PHG in Indian patients.Settings and Design:A case–control study was conducted at a trichology clinic in Bengaluru between October 2013 and April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 9 publications
2
40
0
Order By: Relevance
“…Al-Hamamy et al (13) reported that the peak onset of hair greyness was the fourth decade in people with metabolic syndrome, while it was the fifth decade in those without, which suggests that people with metabolic syndrome tend to develop grey hair earlier. Chakrabarty et al (14) compared various biochemical parameters between 37 cases of PHG (aged 15-25 years) and 37 age-and gendermatched controls, and found that HDL-cholesterol was lower in the PHG group than in the control group. These studies also support the association between metabolic syndrome and hair greying, although Al-Hamamy's study had limitations, such as the lack of age-control in the study population and the possibility of recall bias about the onset of hair greying.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Hamamy et al (13) reported that the peak onset of hair greyness was the fourth decade in people with metabolic syndrome, while it was the fifth decade in those without, which suggests that people with metabolic syndrome tend to develop grey hair earlier. Chakrabarty et al (14) compared various biochemical parameters between 37 cases of PHG (aged 15-25 years) and 37 age-and gendermatched controls, and found that HDL-cholesterol was lower in the PHG group than in the control group. These studies also support the association between metabolic syndrome and hair greying, although Al-Hamamy's study had limitations, such as the lack of age-control in the study population and the possibility of recall bias about the onset of hair greying.…”
Section: Discussionmentioning
confidence: 99%
“…Hair graying is associated with various autoimmune disorders including vitiligo and several rare premature aging syndromes including the Hutchinson Gilford and Werner'syndrome 7 . Hair graying may also reflect nutritional deficiencies (especially of vitamins) and the use of drugs such as chloroquine 8 9 10 . We do not know exactly the cause of hair graying in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of scalp regional graying development did not essentially differ between sexes but more males (75.5%) had hair graying initially involving the parietal areas than in the females whose regional graying patterns were mostly equally distributed all over the scalp regions. behaviors such as smoking and sedentary life style were reported by a huge proportion of participants [8,15,16] whereas some other studies established a weak association or no association at all [17]. The consequential psychological effects to the sufferers were enormous among the participants of the present study.…”
Section: Resultsmentioning
confidence: 48%